Evaluation of an intervention to reduce adolescent sitting time during the school day: The 'Stand Up for Health' randomised controlled trial. Issue 12 (December 2018) - Parrish, Anne-Maree; Trost, Stewart G.; Howard, Steven J.; Batterham, Marijka; Cliff, Dylan; Salmon, Jo; Okely, Anthony D.
Abstract: Objectives: Adolescents spend large proportions of the school day sitting; potentially increasing their health risks. This study aimed to evaluate the feasibility, acceptability and potential efficacy of a school-based intervention to reduce adolescent sitting time during the school day. Design: Two-arm parallel-group randomised controlled trial. Methods: Adolescents (13–16 years) were recruited from four private high schools in New South Wales, Australia. Schools were pair-matched and randomised to treatment or control. Research assistants were blinded to intervention aims and treatment allocation. Intervention initiatives included classroom and outdoor environmental measures to break up and reduce the proportion of adolescent school time spent sitting. Teacher and students surveys assessed intervention feasibility, acceptability and potential efficacy. Proportional sitting time was the primary outcome, measured by activPAL monitors, worn for one week during the school day. Secondary outcomes included body mass index, body fatness, working memory and non-verbal reasoning. Data were analysed using a general linear model for continuous variables and adjusted for clustering. Results: While teachers and students supported the program, process evaluation results indicate aspects of the intervention were not implemented with fidelity. Eighty-eight adolescents ( Mage = 14.7 ± 0.7, 50% male) participated in the trial. Eighty-six had valid data for all variables (43 controls, 43 intervention). There was no significant intervention effect on the primary outcome. There was a significant effect on working memory (adjusted difference ± SD = −0.42 ± 1.37; p = 0.048 (Cohen's d ) = 0.31). Conclusions: These findings contribute to limited research in this area, providing guidance for future interventions in the high school environment. Trial registration: The study was registered with the Australian and New Zealand Clinical Trials Registry (ACTRN 12614001001684).